URGENSI PENGATURAN PARTISIPASI MASYARAKAT DALAM MEWUJUDKAN PEMILU DEMOKRATIS - Azkiya, Ach Mawardi (Legal Studies Journal, 2023)
This article discusses the regulation of public participation in elections, and how urgent it is in realizing democratic elections. Community participation is very important in the implementation of general elections in the process of selecting members of the legislature and executive. Because after all, the community has a fairly large share in the general election process where the community as voters determines the winner in the general election process. In addition to participating in elections, the public is also required to participate in supervising the election process, so that elections run in a quality, integrity and democratic manner. Keywords: Governance, Public Participation and Democratic Elections